Utilization Of Quality Cost Report On Quality Improvement Program In Order To Production Cost Efficiency At The Company - Daeng GS, Achmad; Mahjudin, Mahjudin (JOURNAL OF ECONOMIC SCIENCE, 2015)
Utilization of quality cost report can be used as an assessment tool of management performance in the implementation of quality improvement program. Quality cost report is a form of report that containing the quality costs that incurred in order to the operational of quality improvement program. With the utilization of this quality cost report it is expected to be able to measure the effectiveness of quality improvement program at the company. This research was conducted at the company of sport wear in Surabaya. The method that used is qualitative. The data analysis technique that used is the ratio of the percentage of the quality cost to the total sales so that it can be known the effectiveness of quality improvement program to the increasing of sales volume. The results showed that in 2012, the percentage of the quality cost to the total sales is 2.95%, which indicates a lower level of effectiveness of the standards that set by the company, that is 2.5%. In 2013, the quality improvement program is able to demonstrate that through the quality, sales volume can be increased to reduce the percentage of the quality cost to the sales that is 2.63%. Although not yet reached the standard of improvement that have been set by the company in 2013, the quality improvement program remains implemented in 2014. The effectiveness of quality improvement program is starting showing the good change that is there are the increasing performances of this program by achieving percentage of the quality cost to the sales by 2.44%.